PERPUSTAKAAN DALAM DIMENSI MANAJEMEN PENGETAHUAN - Rizki Nurislaminingsih; Arnila Purnamayanti (Metakom, 2020)
The library is known as an information provider institution. Activities in libraries tend to revolve around procurement, storage and information services, not yet on knowledge management. Indeed knowledge is created from information, and vice versa, from knowledge will produce information. However, knowledge management has emerged from the economic and business world. Therefore this paper aims to dig deeper into the role and position of the library in the knowledge management dimension. This paper uses the literature study method, which is the source and method of data collection by taking data in the library, reading, recording, and processing research material. The results of this paper study are the library is a knowledge institution that also carries out the task of knowledge management. Librarians play the role of knowledge managers whose main task is to trace, select, sort, store and disseminate various types of knowledge. Librarians change the tacit knowledge that still exists in a person to expilcit, then the librarian explains the core of explicit knowledge in the library collection to the librarian. The conclusions of this study are the library is part of knowledge management. Libraries act as knowledge institutions and librarians automatically become workers / managers of knowledge. Furthermore the library processes the tacit knowledge into explicit knowledge, so that it is easily accessed, understood and utilized by the wider community